2018
DOI: 10.1044/2017_ajslp-17-0104
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Peer Interaction for Preschool Children With Complex Communication Needs and Autism Spectrum Disorder

Abstract: https://doi.org/10.23641/asha.5829678.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…It is also unclear whether the children who used AAC had been provided with optimal levels of AAC support, and it is possible that different AAC systems may have resulted in different results. For example, Therrien and Light (2018) reported that the use of visual scene displays (digital images with programmed hotspots that act as communication supports; Light & McNaughton, 2012) resulted in increased interaction between children with characteristics of ASD and their typically developing peers during a story book activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear whether the children who used AAC had been provided with optimal levels of AAC support, and it is possible that different AAC systems may have resulted in different results. For example, Therrien and Light (2018) reported that the use of visual scene displays (digital images with programmed hotspots that act as communication supports; Light & McNaughton, 2012) resulted in increased interaction between children with characteristics of ASD and their typically developing peers during a story book activity.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in social reciprocity are a core characteristic of individuals with ASD (Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition), yet intervention research to improve this more advanced communication skill for young children is sparse. Results of this study expand on the emerging reports of increased turn-taking and child-peer engagement following SGD interventions (Therrien & Light, 2018;Thiemann-Bourque et al, 2018, 2017 To communicate successfully in peer interactions, children need to learn a diverse repertoire of modalities and communicative functions. Unique to this study was the reporting of intervention effects on communication modalities and functions, variables rarely reported in the AAC literature (Logan et al, 2017).…”
Section: Discussionmentioning
confidence: 59%
“…The intervention increased symbolic communicative turns for one child during interactions with three peers; however, results were not replicated for the second child. In a follow-up study, these authors examined effects of a similar intervention package for five preschoolers with characteristics of ASD and trained peers as well as measured rates of peer turns and joint engagement (Therrien & Light, 2018). Effects on peer behaviors have received less attention in the literature, which is a major concern given that changes in reciprocity are dependent on peer behavior changes.…”
Section: Aac Interventions and Peer Partnersmentioning
confidence: 99%
“…It is especially positive to note the gains for children with ASD during interactions in which the peers acted as natural play partners, rather than as instructors, during typical EC activities (e.g., manipulative play, dramatic play). 49,50 In developing interventions focused on preschool-age participants, five supports identified by Hunt et al 1 appear to positively impact the communication outcomes of children with ASD: (1) providing friendship training and ability awareness to peers, (2) identifying interactive materials using the interests of the child with ASD, (3) supporting the use of AAC within preschool activities, (4) using interactive activities to facilitate social communication, and (5) utilizing adult support behaviors to model and promote communication and interaction for both the peer and the child with ASD. Continued research is needed to develop and refine developmentally appropriate partnertraining techniques across a broad range of activities; however, the SMRS evidence score of 3 provides support for the use of this technique with children with ASD.…”
Section: Resultsmentioning
confidence: 99%